Recent Advances in Laboratory Diagnosis of Rabies: Challenges, Innovations, and Future Directions - Raed Yahya Mohammed Garawy,; Hajer Ali Alshamrani,; Salha ali bakeet alyami,; Abdullah Ayed Abdullah Alqahtani,; Faisal Fahd Awdah Aljehani,; Abdulmajeed Obaidallah Kulaib Alharbi,; Sami Mohammed Fahd Alotaibi,; Turki Mshabbab saeed Algahtani,; Shwog Eissa Yehya Fagehi,; Samirah Sheraz Almalki,; Nasser Mohammed Al-Mutairi,; Mohammed hajar mohammed almuntasheri, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Rabies is a fatal zoonotic disease that remains a significant public health challenge, especially in low- and middle-income countries. Accurate and timely laboratory diagnosis is critical for rabies surveillance, clinical management, and guiding post-exposure prophylaxis (PEP). Traditional diagnostic methods, such as the direct fluorescent antibody (DFA) test and mouse inoculation test (MIT), have long served as gold standards but are limited by their reliance on invasive sample collection, specialized infrastructure, and trained personnel. Recent advancements in molecular, antigen detection, and serological techniques have revolutionized rabies diagnostics. Molecular methods, such as reverse transcription polymerase chain reaction (RT-PCR) and loop-mediated isothermal amplification (LAMP), enable rapid and sensitive detection of viral RNA, even in resource-limited settings. Similarly, antigen detection innovations, including the direct rapid immunohistochemical test (DRIT) and immunochromatographic tests (ICTs), provide practical, field-deployable alternatives to traditional approaches. Serological assays, such as the rapid fluorescent focus inhibition test (RFFIT) and enzyme-linked immunosorbent assays (ELISA), have advanced the evaluation of immune responses and vaccine efficacy. Despite these advancements, challenges such as limited access to diagnostic facilities, high costs, and logistical barriers persist in endemic regions. Innovations like point-of-care testing, genomic technologies, and artificial intelligence (AI) show promise for overcoming these hurdles. This review highlights recent advances and ongoing challenges in rabies diagnostics, emphasizing the importance of strengthening laboratory infrastructure and adopting a One Health approach to support global rabies elimination efforts by 2030.